EFEKTIFITAS MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) TERHADAP PRESTASI BELAJAR MAHASISWA MATEMATIKA UST YOGYAKARTA PADA MATA KULIAH PENGOLAHAN DATA STATISTIK - Praja Achsani Winasmadi (Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of this study was to determine the Mathematics Education students are taught by UST Yogyakarta models Missouri Mathematics Project (MMP) achieve mastery learning mathematics, and to know the mathematics achievement of students taught using a model of Missouri Mathematics Project (MMP) is better than being taught by using a model conventional. The study was conducted in Mathematics Education Program FKIP-UST. The population in the study were all students of 7th semester of mathematics education and the samples taken at random from the population consisting of one experimental class and one control class. Data collection method used was a test. The research instrument used to learn math achievement tests. Tests carried out using a test instrument validity and reliability of the data obtained 4 about valid and reliable because more than r table = 0.316. Data analysis using the t test. The results showed the One-Sample Test sig obtained experimental class 0.001> 0.005, then H0 is rejected. So the average value of the experimental class learning model using MMP was 75.8 and achieve mastery learning which is more than 70. In addition, t-test for Equality of Means generate value t = 2.78 and sig (2-tailed) = 0.007 <0.05, so that H1 is accepted. Thus, the average achievement of different experimental class learning achievement grade control. Then based on the output of Group Statistics show the average results of studying experimental class 75.83 is much greater than the control class 67.93. Therefore, it can be concluded that the mathematical achievement of students taught by UST Yogyakarta Missouri Mathematics Project model reached mastery learning and better than students who were taught using the conventional model.